The role of parenting stress in anxiety and sleep outcomes in toddlers with congenital heart disease - Lepage, Charles; Gaudet, Isabelle; Doussau, Amélie; Vinay, Marie-Claude; Gagner, Charlotte; von Siebenthal, Zorina; Poirier, Nancy; Simard, Marie-Noëlle; Paquette, Natacha; Gallagher, Anne (Frontiers in Pediatrics, 2023)
Objectives: This retrospective cohort study investigates how parenting stress, measured at 4 months of age by use of a classic three-dimensional parent-reported scale (Parenting Stress Index, 4th Ed. or PSI-4), can predict anxiety symptoms and quality of sleep at 24 months in toddlers with congenital heart disease (CHD). Study Design: Sixty-six toddlers (42 boys) with CHD were included in this study. All are patients at the cardiac neurodevelopmental follow-up clinic of the Sainte-Justine University Hospital. As part of the systematic developmental assessment program, parents completed questionnaires on their stress level (PSI-4) when their child was 4 months old, and on their child’s anxiety symptoms and quality of sleep at 24 months. Eight multiple linear regression models were built on the two measures collected at 24 months using the PSI-4 scores collected at 4 months. For each measure, four models were built from the PSI-4 total score and its three subscales (Parental Distress, Parent-Child Dysfunctional Interaction, Difficult Child), controlling for sex and socioeconomic status. Results: The PSI-4 Difficult Child subscale, which focuses on parenting anxiety related to the child’s behavioral problems and poor psychosocial adjustment, accounted for 17% of the child’s anxiety symptoms at 24 months. The two other PSI-4 subscales (Parental Distress and Parent-Child Dysfunctional Interaction) and the PSI-4 total score did not contribute significantly to the models. None of the four regression models on perceived quality of sleep were significant. It is important to note that 33% of parents responded defensively to the PSI-4. Conclusions: Parenting stress related to the child’s behavioral problems and poor psychosocial adjustment, measured when the child is 4 months old, is associated with the child’s ulterior anxiety symptoms. As very few standardized tools are available to assess the behavioral and psychoaffective development of infants, this study highlights the importance of early psychosocial screening in parents of infants with CHD. The high rate of defensive responses reminds us to not take parent reports at face value, as their actual stress levels might be higher. The next step will be to develop early interventions that are aimed at reducing parenting stress, thus promoting healthy child development.